MERACIK PELUANG BISNIS INOVATIF PADA KOMODITI TANAMAN DAN HIJAUAN PAKAN - L. Abdullah (Udayana University)
The crops and forage have multifunction as typical nutrients of forage and also the ecosystem component to protect environment preservation, besides for the beauty of landscape, sanitary, cosmetic for livestock and also humans. Human knowledge concerning on crop and forage benefits have been changing commodity into a more valuable economic for market access. Crops and forage as commodities need to be produced and developed. In addition, they should also be supported by forage seed industry and innovation that could raise possitive values. The research and development was carried out to achieve information related to production technology, positive value of innovation on commodity development, efficient use of product and market information control that need to be supported in order to strengthen both positions of commodities in business.